2012
DOI: 10.5539/jfr.v1n3p1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Antioxidant Properties in Organic and Conventional Blueberries

Abstract: Vacciniumcyanococcus, most commonly known as blueberry, is a fruit native to North America that is known for its unique taste and high antioxidant content. The skin, seed and juice of both organically and conventionally grown blueberry extract were analyzed for antioxidant content using both the Hydrophilic and Lipophilic Oxygen Radical Absorbance Capacity (ORAC) assays. Results from the Hydrophilic ORAC test showed that conventionally grown blueberries had a higher antioxidant capacity across all samples, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Lowest levels of antioxidants were observed in the presence or absence of mineral fertilizers. These results are in agreement with several authors those who reported that mineral nutrition has little or no effect on the production of polyphenols and antioxidants in some plants (Pavla & Pokluda, 2008;Gupta-Elera et al, 2012;Marilou et al, 2012). Premuzic et al (2001) found in cherry tomato that vitamin C (a powerful antioxidant) content was higher under organic fertilization or fertilization combining mineral and organic inputs than under exclusive mineral fertilization.…”
Section: Resultssupporting
confidence: 93%
“…Lowest levels of antioxidants were observed in the presence or absence of mineral fertilizers. These results are in agreement with several authors those who reported that mineral nutrition has little or no effect on the production of polyphenols and antioxidants in some plants (Pavla & Pokluda, 2008;Gupta-Elera et al, 2012;Marilou et al, 2012). Premuzic et al (2001) found in cherry tomato that vitamin C (a powerful antioxidant) content was higher under organic fertilization or fertilization combining mineral and organic inputs than under exclusive mineral fertilization.…”
Section: Resultssupporting
confidence: 93%
“…So far, many scientific studies have been carried out comparing integrated/conventional and organic strawberry [17,18,19] and blueberry production [20,21,22,23]. In this way You et al [24] showed that organically grown berries have significantly higher levels of bioactive compounds compared to berries from integrated production.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of organic fertilizers in Org and Org-Min treatments had a stimulating impact on TPC in the fruit (139.8 and 139.3 mg eq GA 100 g -1 FW, respectively). Numerous studies also confirm the fact that blueberries grown under the organic cultivation system have more polyphenols as well as other antioxidant compounds than blueberries grown under the conventional system (Wang et al, 2008;You et al, 2011;Gupta-Elera et al, 2012). Higher values of TPC were also found in strawberries treated with biofertilizers (Pešaković and Milivojević, 2014) which can be explained by highly intensive mineralizing processes in the substrate and the increased physiological functions and activity of the plant root.…”
Section: Resultsmentioning
confidence: 82%